Integrating Earth history into phylogenetic diversification models - Alexis Licht; Isabel Sanmartín; Andrea S. Meseguer; Lydian Boschman; Bram Vaes; Ignacio Quintero; Helene Morlon; K. Christopher Beard (Trends in Ecology & Evolution, 2026)

Population divergence associated with spatial asynchrony in precipitation in Neotropical frogs - Carlos E. Guarnizo; Paola Montoya; Ignacio Quintero; Carlos Daniel Cadena (Journal of Biogeography, 2022)
Aim The role that geography plays in promoting speciation by spatially isolating populations has been studied extensively, but less attention has been devoted to assessing the role of isolation by time mediated by spatial variation in climate as a mechanism promoting population divergence. Gene flow between populations differing in their reproductive schedules might be reduced relative to that between populations with overlapping breeding seasons, potentially leading to genetic divergence. Assuming that precipitation influences reproductive schedules, we explored the effect of asynchronous precipitation regimes on intraspecific genetic divergence. In addition, we examined whether microevolutionary processes are reflected in macroevolutionary patterns by assessing whether regions with more asynchronous precipitation across space have higher frog species richness and have experienced greater speciation rates than regions with more spatially synchronous precipitation regimes. Location Central and South America. Taxon Anurans: across 38 species of Neotropical frogs. Methods For microevolutionary analyses, we assessed the relationship between spatial asynchrony in precipitation and mitochondrial DNA genetic divergence accounting for ecological connectivity using multiple regression and phylogenetic meta‐analyses. For macroevolutionary analyses, we assessed the relationship between species richness, speciation rates estimated from a comprehensive molecular phylogeny, and the degree of spatial asynchrony in precipitation using generalized linear models. Results We found that spatial asynchrony in precipitation is positively associated with genetic differentiation in 39% of the species tested, resulting in a weak cross‐species effect. However, the effect of asynchrony in precipitation on population divergence seems not to scale to macroevolutionary patterns because spatial asynchrony in precipitation was not associated with geographical patterns of species richness nor speciation rates. Main Conclusions Our results indicate that asynchronous breeding may promote genetic divergence even in the absence of geographical barriers in species where breeding is associated with water availability, but such effects may not be stable enough through time to influence macroevolutionary patterns.

Nest architecture is linked with ecological success in songbirds - Iliana Medina; Daniela M. Perez; Ana C. Afonso Silva; Justin Cally; Constanza León; Odile Maliet; Ignacio Quintero (Ecology Letters, 2022)
Nests are essential constructions that determine fitness, yet their structure can vary substantially across bird species. While there is evidence supporting a link between nest architecture and the habitat a species occupies, we still ignore what ecological and evolutionary processes are linked to different nest types. Using information on 3175 species of songbirds, we show that—after controlling for latitude and body size—species that build domed nests (i.e. nests with a roof) have smaller ranges, are less likely to colonise urban environments and have potentially higher extinction rates compared to species with open and cavity nests. Domed nests could be a costly specialisation, and we show that these nests take more time to be built, which could restrict breeding opportunities. These diverse strands of evidence suggest that the transition from domed to open nests in passerines could represent an important evolutionary innovation behind the success of the largest bird radiation.

In Silico Hemodynamics and Filtering Evaluation of a Commercial Embolic Protection Device - Antonio Gil; Pedro Quintero; Andrea Mares; Juan Ribera de Serra; Manuel Ignacio Sánchez-Nevárez; Manuel Miralles (Annals of Biomedical Engineering, 2021)

Global functional and phylogenetic structure of avian assemblages across elevation and latitude - Marta A. Jarzyna; Ignacio Quintero; Walter Jetz (Ecology Letters, 2021)
Mountain systems are exceptionally species rich, yet the associated elevational gradients in functional and phylogenetic diversity and their consistency across latitude remain little understood. Here, we document how avian functional and phylogenetic diversity and structure vary along all major elevational gradients worldwide and uncover strong latitudinal differences. Assemblages in warm tropical lowlands and cold temperate highlands are marked by high functional overdispersion and distinctiveness, whereas tropical highlands and temperate lowlands appear strongly functionally clustered and redundant. We additionally find strong geographic variation in the interplay of phylogenetic and functional structure, with strongest deviations between the two in temperate highlands. This latitudinal and elevational variation in assemblage functional structure is underpinned by nuanced shifts in the position, shape and composition of multivariate trait space. We find that, independent of latitude, high‐elevation assemblages emerge as exceptionally susceptible to functional change.

Corrigendum to Quintero & Wiens (2013) - Ignacio Quintero; John J. Wiens (Ecology Letters, 2013)

Rates of projected climate change dramatically exceed past rates of climatic niche evolution among vertebrate species - Ignacio Quintero; John J. Wiens (Ecology Letters, 2013)
A key question in predicting responses to anthropogenic climate change is: how quickly can species adapt to different climatic conditions? Here, we take a phylogenetic approach to this question. We use 17 time‐calibrated phylogenies representing the major tetrapod clades (amphibians, birds, crocodilians, mammals, squamates, turtles) and climatic data from distributions of > 500 extant species. We estimate rates of change based on differences in climatic variables between sister species and estimated times of their splitting. We compare these rates to predicted rates of climate change from 2000 to 2100. Our results are striking: matching projected changes for 2100 would require rates of niche evolution that are > 10 000 times faster than rates typically observed among species, for most variables and clades. Despite many caveats, our results suggest that adaptation to projected changes in the next 100 years would require rates that are largely unprecedented based on observed rates among vertebrate species.

What determines the climatic niche width of species? The role of spatial and temporal climatic variation in three vertebrate clades - Ignacio Quintero; John J. Wiens (Global Ecology and Biogeography, 2013)
Aim Climatic niche breadth (the range of climatic conditions that a species experiences over space and time) is a fundamental topic in ecology, biogeography and evolution. But what determines the climatic niche width of species? In 1967, J anzen suggested that climatic niche widths for temperature were determined by levels of seasonal fluctuation in temperature at each locality, such that niche breadths are narrow in tropical species and broad in temperate species. However, it is unclear whether climatic niche breadths of species are determined more by seasonal variability within sites as opposed to climatic variation between sites across the species’ range. We address this question here. Location Global. Methods We analysed three vertebrate clades (plethodontid salamanders, hylid frogs and phrynosomatid lizards) for which we had phylogenetic information and climatic data from localities throughout each species’ geographic range, collectively including 409 species. We tested how climatic niche breadths of localities (i.e. temporal variation) are related to overall species climatic niche breadths (i.e. temporal and spatial variation) using phylogenetic comparative methods, focusing both on temperature extremes and precipitation. Results Across the three clades, we find that niche breadths for single localities generally span most of the species’ climatic niche breadth, and are strongly correlated with overall species niche breadths. However, species with wider climatic niches also tend to show greater climatic divergence between localities. Main conclusions The extent to which the climatic niche breadths of species are determined by variation within localities versus spatial variation between localities has been largely unexplored. Our results suggest that within‐locality seasonal variation explains most variation in climatic niche breadths among species. However, between‐locality variation and local adaptation may also play some role. These results require more general testing, but have several important implications.